1990
DOI: 10.1007/bf00055239
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical phylogeny of seven Indian species of the montium subgroup of Drosophila

Abstract: Seven species of the montium subgroup of Drosophila found in South India were analysed with polyacrylamide disc electrophoresis. Eleven loci coding for enzymes were surveyed. The genetic distances between species have been measured. The dendrogram revealed three clusters. The first cluster includes D. nagarholensis, D. agumbensis, D. jambulina and D. kikkawai; the second group consists of D. truncata and D. anomelani; while D. mysorensis was the only species of the third group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
7
1
1
Order By: Relevance
“…Most species of the montium subgroup show diversity in having different dot chromosomes. Dot chromosomes of D. jambulina are seen as small metacentric (Shyamala andRanganath 1994, Suma andRanganath 1997) in contrast to the earlier reports of Singh and Gupta (1980) and Baimai (1980) identified as large submetacentric dot in the strains studied by them. Baimai et al (1983) identified the karyotypic variation in D. meridionalis due to variant forms of the micro-chromosomes.…”
Section: Resultscontrasting
confidence: 82%
See 4 more Smart Citations
“…Most species of the montium subgroup show diversity in having different dot chromosomes. Dot chromosomes of D. jambulina are seen as small metacentric (Shyamala andRanganath 1994, Suma andRanganath 1997) in contrast to the earlier reports of Singh and Gupta (1980) and Baimai (1980) identified as large submetacentric dot in the strains studied by them. Baimai et al (1983) identified the karyotypic variation in D. meridionalis due to variant forms of the micro-chromosomes.…”
Section: Resultscontrasting
confidence: 82%
“…Of the two pairs, the first pair (M1) is longer than the second pair (M2) and their relative length ranges from 281 to 342, while it is 231 to 305 for the second pair (Table 1) The species under study have shown high degree of disparity in the quantity and the distribution of heterochromatin within their genome (Fig. 6) The heterochromatin is believed to have played a significant role in chromosomal evolution in higher organisms (Baimai 1969, Gatti et al 1976, Holmquist 1975, Pathak et al 1973, Yunis and Yasminich 1971, Shyamala and Ranganath 1994, Suma and Ranganath 1997. The amount and position of the heterochromatin influence various attributes of the cell functions like selective advantage (Halfer 1978, Halfer et al 1980) and occurrence of inversions (Baimai 1977).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations